2013
DOI: 10.21608/jfds.2013.72104
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Antimicrobial Activity of Pullulan Edible Films Incorporated With Nanoparticles and Essential Oils and Their Impact on Turkey Deli Meat Quality

Abstract: Edible films containing antimicrobials are gaining importance as potential treatment to extend product shelf life and reduce risk of pathogens. Antimicrobial activities of pullulan films incorporated silver nanoparticles (Ag NPs) 100 nm, zinc oxide nanoparticles (ZnO NPs) 110 nm, oregano oil (OR) 2% and rosemary oil (RO) 2%, against Listeria monocytogenes and Staphylococcus aureus, were evaluated during the preparation and storage at 4, 25, 37, and 55°C up to 49 days in plate overlay assays (in vitro). Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 47 publications
3
23
0
1
Order By: Relevance
“…Samples packed with the BS/ZnO-N 3% film exhibited a reduction of 0.86 log CFU g À1 after 6 days of storage, whereas other packaging exhibited no inhibitory activity against L. monocytogenes. Similarly, Khalaf et al (2013) reported that pullulan edible films incorporated with ZnO-N had antimicrobial activities against L. monocytogenes in turkey deli meat during storage.…”
Section: Packaging Of Mushrooms With the Bs/zno-n Filmsmentioning
confidence: 89%
“…Samples packed with the BS/ZnO-N 3% film exhibited a reduction of 0.86 log CFU g À1 after 6 days of storage, whereas other packaging exhibited no inhibitory activity against L. monocytogenes. Similarly, Khalaf et al (2013) reported that pullulan edible films incorporated with ZnO-N had antimicrobial activities against L. monocytogenes in turkey deli meat during storage.…”
Section: Packaging Of Mushrooms With the Bs/zno-n Filmsmentioning
confidence: 89%
“…Furthermore, storage temperature of nanocomposite materials plays an important role since it can limit their antimicrobial stability. Khalaf et al [30] investigated the inhibitory potency of pullulan-based films containing silver nanoparticles against S. aureus and L. monocytogenes during 7 weeks of storage at different temperatures: 4, 25, 37, and 55 • C. The authors concluded that in order to maintain sustained bactericidal activity, nanomaterials should be stored at temperatures below 25 • C, as temperatures higher than 25 • C significantly reduced their antimicrobial potency. Table 1 summarized the antimicrobial activity of various biopolymer-based materials containing AgNPs through different preparation methods routes, as well as the size and concentration of AgNPs used.…”
Section: Antimicrobial Properties Of Edible Films and Coatings With Imentioning
confidence: 99%
“…The strains activated at Food Technology Department, Benha University, Egypt. All strains were cultivated twice on Tryptic Soy Agar (TSB; Bio-life company, Italy) at 37°C for 24 h, and kept at 4°C till using [17].…”
Section: Bacterial Strainsmentioning
confidence: 99%